Environmental Impact Assessment of Tourism Activities in Kenyir Lake: A Life Cycle Approach - Dullah H.; Salleh N.S.M.; Zawawi M.H.; Hassan N.H. (EDP Sciences, 2025)
This study evaluates the environmental impacts of tourism activities at Kenyir Lake, focusing on houseboat and resort operations using a Life Cycle Assessment (LCA) approach. The research aims to identify key contributors to environmental degradation by systematically analyzing the inputs and outputs associated with these activities. Primary sources collected through interviews and water sample collection for laboratory analysis, supported by secondary literature, and analyzed using SimaPro 9.1.1.1 software following the CML-IA method, which evaluates ten impact categories. The findings highlight those operations, especially energy consumption and waste management, are significant contributors to environmental impacts, with substantial effects on global warming, ozone layer depletion, and various forms of ecotoxicity. The study emphasizes the need for sustainable practices in tourism operations, particularly in reducing energy use and improving waste management. The results provide critical insights into the sustainability and efficiency of tourism infrastructure at Kenyir Lake, offering valuable recommendations for mitigating adverse environmental impacts and promoting sustainable tourism practices in the region. ? The Authors, published by EDP Sciences.